SOSIALISASI PLATELET RICH PLASMA (PRP) ALOGENIK SEBAGAI TERAPI PENDUKUNG DIABETES MELLITUS PADA TENAGA KESEHATAN DI FASILITAS KESEHATAN KOTA SEMARANG - Della Hashfi Anzhari; Muthia Syafira; Resti Ariani; Anna Kartika Yuli Astuti; Tulus Puji Lestari (JPMUJ, 2026)
Diabetes mellitus is a non-communicable disease with an increasing prevalence and is often accompanied by chronic complications, one of which is diabetic foot ulcers that are difficult to heal and have a high risk of infection and amputation. Conventional management of diabetic wounds often fails to produce optimal results, necessitating innovative and evidence-based supportive therapies. Platelet-Rich Plasma (PRP) is a blood-derived product rich in growth factors that has the potential to accelerate wound healing. Although the potential of PRP has been widely reported, healthcare professionals' understanding and readiness to apply it remain limited, particularly in primary healthcare facilities. This community service activity aims to increase the knowledge and understanding of health workers regarding allogeneic PRP, including topical or spray formulations, as a supportive therapy in the treatment of diabetic wounds. The community service method was carried out through educational and knowledge dissemination activities, which included material presentations, interactive discussions, and demonstrations of the use of PRP on diabetic wounds using simulation media. The activity was carried out at the Indonesian Red Cross in Semarang City, involving health workers from the Indonesian Red Cross and affiliated health care facilities. The material presented covered the basic concepts of PRP, the mechanism of PRP in wound healing, the differences between autologous and allogeneic PRP, and the principles of using topical or spray PRP. Data were obtained through observation during the activity and participant responses, then analyzed using descriptive qualitative methods. The novelty of this activity was the introduction of allogeneic PRP in topical or spray form as a supportive therapy for diabetic wounds to health workers, which is still relatively rarely applied in health service practice. The results of the activity showed an increase in participants' understanding, enthusiasm, and readiness to consider the use of PRP as part of rational and safe diabetes wound management. It was concluded that this community service activity could increase healthcare workers' knowledge of the use of allogeneic PRP as a supportive therapy for diabetic wounds and has the potential to encourage the adoption of evidence-based regenerative therapies in healthcare facilities.